'SAUDI VISION 2030': A VIABLE RESPONSE TO YOUTH ASPIRATIONS AND CONCERNS?. Issue 2 (3rd April 2017) - Thompson, Mark C.
Abstract : Since Deputy Crown Prince Mohammed bin Salman Al Saud unveiled Saudi Vision 2030 (The National Transformation Programme, 25 April 2016) a great deal of analysis has focused on the potential impact of Vision 2030 at the national level. Significantly, Saudi Vision 2030, which promises a better future and better governance, is raising hopes and expectations amongst young well-educated Saudis. Nevertheless, how has Saudi Vision 2030 been interpreted by young educated male Saudis many of whom are struggling to enter the labour market at a time of austerity and economic uncertainty? This paper discusses young male perceptions of Saudi Vision 2030 including their expectations and hopes for the Vision. In fact, an understanding of how young Saudis perceive Vision 2030 is not only pertinent in the Saudi national context (or indeed multiple Saudi domestic contexts), but also has wider regional relevance considering oil-market developments and economic policy.